COVID-19 as a stress test: Assessing the bank regulatory framework - Duncan, Elizabeth; Horvath, Akos; Iercosan, Diana; Loudis, Bert; Maddrey, Alice; Martinez, Francis; Mooney, Timothy; Ranish, Ben; Wang, Ke; Warusawitharana, Missaka; Wix, Carlo (Journal of Financial Stability, 2022)
The broad economic damage of the COVID-19 pandemic poses the first major test of the bank regulatory reforms put in place after the Global Financial Crisis. Our study assesses the U.S. regulatory framework, with an emphasis on capital and liquidity requirements. Prior to the COVID-19 crisis, banks were well capitalized and held ample liquid assets, which partly reflects enhanced requirements. The overall robust capital and liquidity levels resulted in a resilient banking system, which maintained lending and market making through the early stages of the pandemic. Trading activity was a source of strength for banks, reflecting in part a prudent regulatory approach. That said, leverage requirements are associated with more repo position netting by banks, with potential implications for market making.